DETERMINATION OF VALUES OF TECHNOLOGICAL PARAMETERS OF THE PRODUCTION PROCESS AND CHARACTERISTICS OF THE PRODUCTS PRODUCED UNDER STANDARD DIN 10025 FOR ESTABLISHMENT OF DELIVERY STATE (N OR AR) - V. A. Politov; O. M. Kirilenko; P. K. Grobovskij (Литьë и металлургия, 2010)
The values of technological parameters of the production process and characteristics of rolled production, produced at mill 850, are established and allow to determine the state of hot-rolled rounds.